APECED‐Associated Hepatitis: Clinical, Biochemical, Histological and Treatment Data From a Large, Predominantly American Cohort. Issue 3 (17th March 2021) - Chascsa, David M.; Ferré, Elise M. N.; Hadjiyannis, Yannis; Alao, Hawwa; Natarajan, Mukil; Quinones, Mariam; Kleiner, David E.; Simcox, Thomas L.; Chitsaz, Ehsan; Rose, Stacey R.; Hallgren, Asa; Kampe, Olle; et al.
Abstract : Background and Aims: Autoimmune polyendocrinopathy‐candidiasis‐ectodermal dystrophy (APECED), caused by autoimmune regulator ( AIRE ) mutations, manifests with chronic mucocutaneous candidiasis (CMC) and multisystem autoimmunity, most often hypoparathyroidism (HP) and adrenal insufficiency (AI). European cohorts previously reported a 10% prevalence of APECED‐associated hepatitis (APAH) with presentations ranging from asymptomatic laboratory derangements to fatal fulminant hepatic failure. Herein, we characterized APAH in a large APECED cohort from the Americas. Approach and Results: Forty‐five consecutive patients with APECED were evaluated (2013‐2015) at the National Institutes of Health (NIH; NCT01386437). Hepatology consultation assessed hepatic and autoimmune biomarkers and liver ultrasound in all patients. Liver biopsies evaluated autoimmune features and fibrosis. The 16S ribosomal RNA (rRNA) sequencing was performed in 35 patients' stools (12 with and 23 without APAH). Among 43 evaluable patients, 18 (42%) had APAH; in 33.3% of those with APAH, APAH occurred before developing classic APECED diagnostic criteria. At APAH diagnosis, the median age was 7.8 years, and patients manifested with aminotransferase elevation and/or hyperbilirubinemia. All patients with APAH were in clinical remission during their NIH evaluation while receiving immunomodulatory treatment. We found no difference in age, sex, or prevalence of CMC, AI, or HP between patients with or without APAH. Autoantibody positivity against aromatic L‐amino acid decarboxylase, cytochrome P450 family 1 subfamily A member 2, histidine decarboxylase (HDC), bactericidal/permeability‐increasing fold‐containing B1, tryptophan hydroxlase, and 21‐hydroxylase (21‐OH), and the homozygous c.967_979del13 AIRE mutation were associated with APAH development. Classical serological biomarkers of autoimmune hepatitis (AIH) were only sporadically positive. AIH‐like lymphoplasmacytic inflammation with mild fibrosis was the predominant histological feature. Stool microbiome analysis found Slackia and Acidaminococcus in greater abundance in patients with APAH. Conclusions: APAH is more common than previously described, may present early before classic APECED manifestations, and most often manifests with milder, treatment‐responsive disease. Several APECED‐associated autoantibodies, but not standard AIH‐associated biomarkers, correlate with APAH.